The Role of Public Health in Addressing Racial and Ethnic Disparities in Mental Health and Mental Illness - Annelle B. Primm, MD, MPH; Melba J. T. Vasquez, PhD; Robert A. Mays, PhD, MSW; Doreleena Sammons-Posey, SM; Lela R. McKnight-Eily, PhD; Letitia R. Presley-Cantrell, PhD; Lisa C. McGuire, PhD; Daniel P. Chapman, PhD, MSc; Geraldine S. Perry, DrPH, RD (Centers for Disease Control and Prevention, 2010)
Racial/ethnic minority populations are underserved in the American mental health care system. Disparity in treatment between whites and African Americans has increased substantially since the 1990s. Racial/ethnic minorities may be disproportionately affected by limited English proficiency, remote geographic settings, stigma, fragmented services, cost, comorbidity of mental illness and chronic diseases, cultural understanding of health care services, and incarceration. We present a model that illustrates how social determinants of health, interventions, and outcomes interact to affect mental health and mental illness. Public health approaches to these concerns include preventive strategies and federal agency collaborations that optimize the resilience of racial/ethnic minorities. We recommend strategies such as enhanced surveillance, research, evidence-based practice, and public policies that set standards for tracking and reducing disparities.